Analisis Pengisian Baterai Aki Kendaraan Listrik Menggunakan Sumber Daya dari Panel Surya dan PLN - Unang Achlison; Joseph Teguh Santoso; Khoirur Rozikin; Silalahi, Fujiama Diapoldo (Elkom: Jurnal Elektronika dan Komputer, 2024)
Electric vehicles use a power source from electrical energy to be converted into kinetic energy. The electrical energy source is stored in the battery. The battery charging process can be done using power sources from Solar Panels and PLN. Based on the analysis of the measurement results, it can be concluded that (1) recharging the battery using Solar Panels from minimum to maximum conditions takes 4 hours 38 minutes, and (2) recharging the battery using PLN from minimum to maximum conditions takes 2 hours.